2000
DOI: 10.1001/archfami.9.9.898
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simvastatin Treatment in Patients With Combined Hyperlipidemia in Clinical Practice

Abstract: Multiple factors contribute to LDL-C goal achievement in a usual care setting. A significant opportunity exists to increase the number of patients who achieve LDL-C goal by appropriate dose titration and/or give patients a higher initial dose of simvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…16 -18 Patients with diabetes taking a lipid-lowering drug were more than 3 times as likely to have achieved the LDL goal specified by the ADA. Previous studies, however, have found that even among patients using a lipid-lowering drug, many do not achieve the LDL cholesterol goal 19,20 ; in one study, the majority of patients who were currently using a lipid-lowering drug had not achieved goal. 21 In almost all cases, patients were not taking the maximum drug dose, suggesting that inadequate dosing may be one explanation for failure to achieve goal.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…16 -18 Patients with diabetes taking a lipid-lowering drug were more than 3 times as likely to have achieved the LDL goal specified by the ADA. Previous studies, however, have found that even among patients using a lipid-lowering drug, many do not achieve the LDL cholesterol goal 19,20 ; in one study, the majority of patients who were currently using a lipid-lowering drug had not achieved goal. 21 In almost all cases, patients were not taking the maximum drug dose, suggesting that inadequate dosing may be one explanation for failure to achieve goal.…”
Section: Discussionmentioning
confidence: 89%
“…The HDL goal may be more difficult to achieve because many commonly used lipid-lowering drugs are more effective at lowering LDL cholesterol than they are at raising HDL cholesterol. 20 In addition, diabetes-related inhibition of lipoprotein lipase often leads to elevated levels of triglyceride and reduced levels of HDL cholesterol, which may persist even with good glycemic control. 22 There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…LDL-C measurement and the percentage of CHD patients at LDL-C goal increased after reminders were initiated, suggesting that reminders can be an effective tool in improving cholesterol management of CHD patients in primary care settings. Although these patients were treated, a higher percentage of patients could achieve LDLX goal with appropriate lipid medication, a higher initial dose, or adequate dose titration (Pearson & Peters, 1997;Vicari et al, 2000). One reason why more patients who receive treatment do not reach LDL-C: goal is they may need a larger reduction in LDLC levels than many pharmacotherapies can provide at usual initial doses ("Simvastatin," 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Statins are very effective in reducing LDL-C, but do not always correct increased TGRL [6]; on the other hand, fibrates markedly lower plasma total triglycerides (TGs), but modestly lower total cholesterol (TC) and LDL-C [7]. Given that combination therapy with statin plus fibrate confers an increased risk of myopathy and rhabdomyolysis [8], a possible alternative might be to use more potent statins.…”
Section: Introductionmentioning
confidence: 99%